New amino acid modifications in porins of Gram negative isolates contributing to carbapenem resistance - Simões, Constança (2017)
Objectives: Carbapenems are a group of β-lactam antibiotics that constitute one of the last resorts in the treatment of infections caused by Gram negative bacteria. Considering the emerging rates of resistance to these antibiotics, the investigation of its mechanisms constitutes an important assignment. Thus, this study aimed to characterize the carbapenem resistance mechanisms harboured by Gram-negative isolates. Methods: A total of 426 isolates were screened to the susceptibility to ertapenem by disc diffusion (interpreted by SFM guidelines). Non-susceptible isolates were retained and studied against other classes of antibiotics, using the same phenotypic method. Mechanisms justifying the resistance to carbapenemes were searched: Carbapenemase (CARB) production, by using molecular methods and isoelectric focusing, and modification of outer membrane porins (Omp), by the profile of Omps, after migration in SDS-PAGE: OmpK35, OmpK36, OmpK37 for 15 Klebsiella pneumoniae, OmpC, OmpF for 1 Escherichia coli, 1 Enterobacter cloacae and 1 Enterobacter cancerogenus, Omp35 and Omp36 for 4 Enterobacter aerogenes. The complete characterization of Omp-encoding genes was performed by PCR amplification and sequencing. Deduced amino acid modifications were interpreted by comparing both clinical and wild-type sequences, using the EMBL database. In addition to CARB-encoding genes, other bla genes were also searched by PCR and sequencing. Results: Among the 426 isolates studied, 22 (5%) revealed to be non-susceptible to ertapenem and were subsequently retained to further investigations. The antibiotic susceptibility evaluation enabled the prediction of the respective resistance mechanisms and guided the remaining biochemical and molecular studies; it also revealed that 4% of the isolates were multidrug resistant. In the 22 isolates we characterized 3 KPC-3 (pI 6.7) and 1 GES-5 (pI 5.8) carbapenemases. In 21 out of 22 isolates, amino acid substitutions were identified due to insertions, deletions and/or mutations in the nucleotide sequence of Omp-encoding genes. Overall, we detected modifications of amino acid sequence in the main regions related to the porin functions, suggesting a role in carbapenem resistance, namely the loops L1, L2 and L4 (implicated in the monomer-monomer relations), loop L3 (acting at constriction zone), loop L5, L6 and L7 (in the surface of the porin) and loop L8 (contributing to the channel opening). It is important to emphasize the CTX-M-15-producing E. coli isolate which showed a new amino acid substitution in loop L3 (Gly116Asp) of porin OmpC, related to carbapenem resistance, and stop codons in porins of K. pneumoniae (in OmpK36 of 4 isolates and OmpK35 in 2), as well as the amino acid substitutions in the loop L3 of OmpK37, and a substitution in loop L8 in porin OmpK36 of 3 K. pneumoniae isolates. Conclusions: Globally, this study provides meaningful insights towards the understanding of emergent carbapenem resistance.